Performance of Relay-Aided Multi-Carrier-CDMA using preprocessing based on quantized feedback. (November 2015) - Nagaradjane, Prabagarane; Muthu, Tamilarasi
Graphical abstract: Highlights: The achievable BER when a DMS is supported by a cluster of relays (PCIRs and VQ-CIRs). The attainable BER when a DMS is assisted by one relay (PCIRs and VQ-CIRs). The achievable BER when one relay assists all the K DMSs (PCIRs and VQ-CIRs). Abstract: In this paper, we investigate the achievable bit-error-rate performance (BER) of a transmitter preprocessing (TP)-aided cooperative downlink (DL) multi-carrier code division multiple access system by employing three cooperation strategies. In a multi-user cooperative DL communication, multi-user interference at the relays, which prevents the achievement of relay diversity, is suppressed with the aid of the TP operated at the base station (BS). In addition, inter-relay interference at the destination mobile station is mitigated by the TP employed at the relays. Furthermore, the channel impulse responses (CIRs) required for formulating the TP at the BS is based on the quantized CIRs feedback in contrast to the perfect CIRs (PCIRs) assumption at the relays. Our study shows that the resultant BER performance of the quantized CIRs feedback-based TP at the BS, coupled with the PCIR-based TP at the relays, remains close to that attained with the PCIRs knowledge at the BS and relays.